PESAN-PESAN MORAL DALAM NOVEL THE COLOR PURPLE KARYA ALICE WALKER - Adolo, Zein; Wantasen, Isnawaty L.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTA moral message is a message or lesson conveyed by the author to the reader or listener directly or indirectly with a spesific purpose for example is the moral messages found in the Novel â€œThe Color Purpleâ€, one of the most popular novels written by Alice Walker in 1982. Most of her writings focus and symbolize the struggles of African-Americans, Particulary woman, and their witness against societies that are racist, sexist, and violent. The problems of this research is : what are the moral messages in â€œThe Color Purpleâ€ and how are the moral messages portrayedÂ in this story. This research use deskriptive method, which describes the extrinsic and intrinsic element in a literary work by using pragmatic theory of Abrams in The Mirror of the Lamp who conceive study literary works that focus on the effects of literary works to the reader. Based on this research, the writer analyzed the moral messages in this novel into two parts, that is Positive moral messages which are describe through several literary media involve: Story of Titles, Main Character,A Supporting Character (Shug Avery, Sophia Butlers), Interaction between Characters (Celie and Nettie, Celie and Shug Avery, Mary Agnes and Sofia). Negative Moral Messages that is Sexual Violence, Free Sex, and Same-sex Relationship (Lesbianism).Â Keywords : The Color Purple, Novel, Moral Messages.